Analisis Kualitas Pelayanan Perusahaan Keagenan Kapal Terhadap Kepuasan Pengguna Layanan Transportasi Laut Di Pelabuhan Teluk Adang Tanah Paser - Turnip, Ricard Mugabe; Dody Efrianto (Jurnal Cakrawala Bahari, 2025)
Maritime transportation plays a strategic role in enhancing connectivity across the Indonesian archipelago, including Teluk Adang Port in Tanah Paser, East Kalimantan. Shipping agencies act as key actors in ensuring smooth vessel operations, covering documentation, logistics provision, and coordination with port authorities. This study analyzes the service quality of shipping agencies in relation to user satisfaction, driven by complaints regarding service delays, unclear administrative fees, and ineffective communication. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The analysis focuses on five SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Findings reveal that reliability and assurance are relatively strong, as reflected in timely document processing and staff competence in delivering services. However, weaknesses remain in responsiveness, empathy, and physical facilities, such as slow complaint handling, inconsistent attention to user needs, limited office facilities, and the continued reliance on manual administrative systems. The study concludes that service quality in shipping agencies significantly influences user satisfaction, highlighting the need to improve non-technical aspects and adopt digital-based facilities for modernization. Theoretically, this research contributes to the study of service quality in the maritime sector, while practically providing insights for shipping agencies and port authorities to enhance service performance through improved responsiveness, user-oriented approaches, and technology-driven systems.